Spectrally Resolved Fiber Photometry for In Vivo Multi‐Color Fluorescence Measurements. Issue 11 (14th November 2022) - Zhou, Jingheng; Yeh, Alan; Meng, Chengbo; Papaneri, Amy B.; Peddada, Teja; Kobzar, Nicholas P.; Cui, Guohong
Abstract: This article describes how to assemble and operate a spectrometer‐based fiber photometry system for in vivo simultaneous measurements of multiple fluorescent biosensors in freely moving mice. The first section of the article describes the step‐by‐step procedure to assemble a basic single‐spectrometer fiber photometry system and how to expand it into a dual‐spectrometer system that allows for simultaneous recordings from two sites. The second part describes the steps for a typical fiber probe implantation surgery. The last section describes how to acquire and analyze the time‐lapsed spectral data. This article is intended for teaching labs how to build their own fiber photometry systems (with a video tutorial) from commercially available parts and perform in vivo recordings in behaving mice. © Published 2022. This article is a U.S. Government work and is in the public domain in the USA. Basic Protocol 1 : Assembling a dual‐laser, single‐spectrometer fiber photometry system Support Protocol : Dual‐spectrometer fiber photometry assembly Basic Protocol 2 : Optical fiber probe implantation Basic Protocol 3 : Data acquisition and analysis